Contribution of Traditional Mehule Games to Improve Understanding of Local Wisdom Material and Students' Interest in Learning Science Subjects in Grade IV of SDN Were'a - Ni Wayan Wahyu Evayanti; Misnah Misnah; Bau Ratu (Journal of Education Method and Learning Strategy, 2025)
Abustang, Waddi Fatimah Perawati Bte. 2020. “The Influence of Learning Interest on Social Studies Learning Outcomes.” 7:1–112.Aqillah, Nurul, Zaini Siti, Nor Ayna, Binti Mohd, Ayu Mohd, Zairul Masron, Faculty of Management, Maklumat Uitm, Cawangan Selangor, Puncak Perdana Campus, Shah Alam, and Selangor Abstract. 2021. "JOURNAL OF MALAYSIAN ORAL HISTORY ISSN 2600-7088 VOL. 5 ISU 2 OCTOBER 2021 The Art of Rotation: Traditional Gasing Pangkah Which Is Increasingly Disappearing." 37–54.Atmaja, Rosko, I. Wayan Ramantha, and I. Wayan Suartana. 2017. “Indicators of Understanding.” E-Journal of Economics and Business, Udayana University 11–35.2024. “Engklek Game Media on Social Studies Learning Outcomes of Elementary School Students at Nahdlatul Ulama University, Surabaya, Indonesia.” 5.Fadia Nurluthfiana, Erlita Umi Masytoh, Silvia Berliana, Wafna Jannata Ulya, Ahmad Hariyadi, Wawan Shokib Rondli, Erik Aditia Ismaya, and Imaniar Purbasari. 2023. “The Importance of Efforts to Increase Interest in Learning Social Studies by Using Audiovisual Media in Lower Elementary School Students at Sd Negeri Kunir 1 Dempet Demak.” Proceedings of the National Seminar on Education, Language, Literature, Arts, and Culture 2(1):375–84. doi:10.55606/mateandrau.v2i1.307.Hadyansah, Diky, Rama Adha Septiana, and Ali Budiman. 2021. “Traditional Games as Local Wisdom Values.” Aksara Raga 3:42.Hati, Dinda Permata, Study Program, Teacher Education, Elementary School, Elementary Education Department, Faculty of Teacher Training, and AND Science. 2019. “The Influence of Problem Based Learning on.” 7:8688–96.Class, Student Learning. 2025. “DIGITAL-BASED SOCIAL STUDIES LEARNING STRATEGY THROUGH BAAMBOOZLE GAME TO IMPROVE INTEREST AT SD NEGERI 2 SAMUDRA KULON.” 5(2):1773–80.Laini, Alif, Wafiq Aziz, and Afraida Hardisa. 2023. “Character Building of Early Childhood in Traditional Pangkak Gasing Games.” VII(Ii):1–8.M Jirana Nurul. 2023. “The Relationship between the TikTok Application and the Learning Interests of PAI Students Class of 2020.” Sipakainge Journal 1(1):31–40.Increasing students' interest in learning through methods. 2024. 09.Mohd Muhaimi, Nur Mastura, Nur Shuhadah Ismail, Nik Azliza Nik Ariffin, and Alwi Mohd Yunus. 2022. “Plate Top Heritage Game.” Malaysian Journal of Oral History 6(2):21–43.Muazimah, Ajriah, and Ida Windi Wahyuni. 2020. “Character Education Based on Local Wisdom Through Traditional Games of Tarik Upih in Improving Children’s Gross Motor Skills.” Golden Generation 3(1):70–76. doi:10.25299/jge.2020.vol3(1).5505.Muliadi, Erlan, and Akhmad Asyari. 2024. “Exploring Local Wisdom: Value Education in Traditional Games of the Sasak Tribe.” Scientific Journal of Educational Professions 9(1):129–40. doi:10.29303/jipp.v9i1.1922.Novitasari, Dewi, and Heni Pujiastuti. 2020. “Analysis of Students’ Conceptual Understanding of Real Analysis Material Based on Bloom’s Taxonomy Reviewed from the Cognitive Domain.” Maju 7(2):153–63.Rahman, B. 2024. “Innovation in Social Studies Learning Through Traditional Game Learning Methods.” … : Journal of Education and Learning 1686.Ramdhan, Asep. 2023. “Preserving the Traditional Sundanese Spinning Top Game in Illustrated Story Books.” 03(2):65–79.Ramkar, RS, F. Septiadi, and B. Bachtiar. 2024. “The Contribution of Traditional Games to Students' Gross Motor Skills: Classroom Action Research.” Indonesian Journal of Physical … 4(2):8–13.Saprima, Tendi, Etriadi, and Nasrullah. 2020. “The Spinning Top Game in Sambas.” Sambas Journal 3(1):13–27.Study, Program, Teacher Education, Madrasah Ibtidaiyah, Faculty of Science, Tarbiyah Dan, Islamic University, and Syarif State University. 2025. “TRADITIONAL GOBAK SODOR IN IPAS TO IMPROVE SOCIAL SKILLS OF STUDENTS OF GRADE IV MIS SA 'ADATUDDARAIN 2 SOUTH TANGERANG CITY.”Thalib, Azizah, and Regita Maulinda. 2021. “Development of Nobangan Learning Model Based on Traditional Games of Kaili Tribe on the Active Value of Grade IV Elementary School Students.” Elementary School: Journal of Elementary School Education and Learning 8(1):199–206. doi:10.31316/esjurnal.v8i1.1103.Widiana, I. Wayan. 2022. “Game Based Learning and Its Impact on Increasing Students’ Interest in Learning and Understanding of Concepts in Science Learning in Elementary Schools.” 10(1):1–10.Windayanti, Windayanti, Mihrab Afnanda, Ria Agustina, Emanuel BS Kase, Muh Safar, and Sabil Mokodenseho. 2023. “Teachers’ Problems in Implementing Independent Curriculum.” Journal on Education 6(1):2056–63. doi:10.31004/joe.v6i1.3197.Yusman, Salsabila Farodis, and Fatiya Rosyida. 2025. “IMPLEMENTATION OF SOCIAL STUDIES LEARNING BASED ON TRADITIONAL BOI-BOIAN GAMES.” 3(2). doi:10.17977/um084v3i22025p309-316.